Development of Interactive Learning Media Based on Open Technology - Siti Nur Aisyiyah Rahman; Ahmad Fauzi Pratama (CV JK Riset Publishing Group, 2025)
This study developed an interactive learning media based on open technology that is pedagogically effective, increasing motivation, engagement, and accessibility for diverse learners in Indonesia. Using a quasi-experimental approach and statistical analysis, it was found that this media significantly improves learning outcomes with a large effect size (d=1.35) and strengthens mastery of higher-order cognitive skills. The use of open source platforms such as Moodle and H5P allows customization to suit local contexts and reduces development costs by up to 70%. Evaluation results show high levels of satisfaction, sustained engagement, and increased learner motivation. These findings support the role of open technology in realizing inclusive and equitable education and provide important implications for education policy related to the development of open source-based digital media. This study contributes to the literature on educational innovation and offers a scalable and sustainable media development model in Indonesia